فاعلية الفهم القرائي في تنمية مهارة التفكير الناقد لدى متعلمي السنة الرابعة متوسط -دراسة ميدانية - قدادره نجاة; شايب منى (University of El-Oued جامعة الوادي, 2025)
تحاول هذه الدراسة أن تدرس مدى فاعلية الفهم القرائي في تنمية مهارات التفكير الناقد لدى متعلمي السنة الرابعة متوسطة، ولتحقيق هدف الدراسة تم استخدام المنهج الوصفي التحليلي وقد تمّ دعم هذا المنهج بأسلوب دراسة استطلاعية عبر أداة الاستبيان مُوجّهه إلى أساتذة اللغة العربية لرصد تصوّراتهم وتقييماتهم لمدى ارتباط الفهم القرائي بتنمية التفكير الناقد. وتم اختيار عيّنة مكوّنة من (26) أستاذ من أساتذة اللغة العربية الذين يدرّسون السنة الرابعة متوسطة. حيث أجريت الدراسة خلال الفصل الأخير من السنة الدراسية (2024–2025)، على (10) متوسطات واقعة في مقاطعة الوادي تابعة لمديرية التربية لولاية الوادي. وخلصت النتائج إلى أن: معظم الأساتذة يدركون الدور الكبير للفهم القرائي في تنمية مهارات التفكير الناقد، وهناك مساهمة إيجابية للفهم القرائي على مهارات التفكير الناقد منها: مهارة التفسير والتحليل والتقييم والاستنتاج. وأن الفهم القرائي يلعب دورًا مهمًا في تمكين التلاميذ من شرح المعلومات بشكل منطقي ومفهوم، وأنه أيضا يلعب دورًا محفّزًا في تنمية مهارة التنظيم الذاتي لدى تلاميذ السنة الرابعة متوسط. This study aims to examine the effectiveness of reading comprehension in developing critical thinking skills among fourth-year middle school learners. To achieve this objective, the descriptive-analytical method was employed, upported by an exploratory study using a questionnaire directed at Arabic language teachers. The goal was to capture their perceptions and evaluations of the extent to which reading comprehension contributes to the development of critical thinking. A sample of 26 Arabic language teachers who teach fourth-year middle school classes was selected. The study was conducted during the final term of the 2024–2025 academic year, across 10 middle schools located in the El-Oued district, under the supervision of the Directorate of Education for El Oued Province. The findings revealed that most teachers recognize the significant role of reading comprehension in fostering critical thinking skills. Reading comprehension has a positive impact on several critical thinking skills, including interpretation, analysis, evaluation, and inference. Additionally, it plays an important role in enabling students to explain information logically and clearly, and it serves as a motivating factor in developing self-regulation skills among fourth-year middle school learners.
مذكرة .ماستر . لسانيات عامة. 2025
Keywords: الفهم القرائي، التفكير الناقد، مهارة التفسير، مهارة التحليل، مهارة التقييم، مهارة الاستنتاج، مهارة الشرح، مهارة التنظيم الذاتي، تلاميذ السنة الرابعة متوسطة.; critical thinking; interpretation skill; analysis skill; evaluation skill; inference skill; explanation skill; self-regulation skill; fourth-year middle school students